DETERMINANTS OF PRICE, IMAGE AND CONVENIENCE TOWARDS CONSUMER PREFERENCE ON FOOD TRUCK BUSINESSES AT SHAH ALAM, SELANGOR - Fahimi Sofian,; Nor Suhaida Awang,; Shazlin Samaan,; Najwa Normazi,; Norhana Saini, (Journal of Islamic, Social, Economics and Development, 2024)
In the food and beverage sector, the food truck business is a particularly competitive field. It is the most convenient dining service and provides a wide range of typical local cuisine. However, to maintain expansion and expand profit margins in this firm, the ability to meet customers’ expectations and requests becomes the most important factor. The purpose of this study is to investigate the factors that influence consumer preference towards food truck business among private university students in shah alam Selangor. Specifically, this study aims to investigate the effect of pricing, image, and convenience on consumer preference towards food truck among private university students. As for methodology, primary data was collected from a sample of 99 students at private university in Shah Alam Selangor using survey instruments. The collected data was analysed using SPSS. The findings revealed that convenience had a significant relationship while price and image had no significant between consumer preference among private university students in Shah Alam Selangor. This research also includes a discussion, limitations, recommendations, and conclusions.